Object Oriented Programming of Application Admission of New High School Students - Yayuk Ike Meilani; Purnama, Jaka (Politeknik Ganesha Medan, 2023)
Abstract: This research was conducted at one of the high schools in Palembang. The admission of new students that are carried out still uses on-site registration so that prospective students must go to school to register. The purpose of implementing object oriented in new student admissions applications is to make the application lighter when using it because the objects are divided into classes. Using the application of oop in application development is useful to make it easier to make applications. The built application can be used for dynamic and flexible new student registration media that can register anywhere and anytime. The concept model used in the application is MVC (Model, View, Controller) which makes it easy for the application to handle errors and bugs due to the structure of the program code used. With the implementation of the oop concept in the program, it is hoped that it can help application development and make it easier to detect errors.